Subunit A of Factor XIII Regulates Subunit B Plasma Concentration - Rodeghiero, F; Morbin, M; Barbui, T (Thrombosis and Haemostasis, 1981)
Subunit a of Factor XIII is found absent in homozygotes and reduced in heterozygotes. Since a concomitant reduction of subunit b occurs in these cases, an interaction between the loci controlling the synthesis of the two subunits was suggested. However in the present study we have shown that the administration of subunit a in two totally devoid homozygotes produced an increase of subunit b, reaching the maximum concentration five days after infusion. This strongly suggests that subunit b plasma level is regulated on the subunit a plasma amount.
Keywords: Blood coagulation Factor XIII; Molecular subunits; Plasma level of Factor XIII